Effect of the administration of probiotic Bacillus NP5 in the rearing media on water quality, growth, and disease resistance of African catfish (Clarias gariepinus) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Putra AN, Syamsunarno MB, Ningrum W, Jumyanah, Mustahal. 2020. Effect of the administration of probiotic Bacillus NP5 in the rearing media on water quality, growth, and disease resistance of African catfish (Clarias gariepinus). Biodiversitas 21: 2566-2575. The purpose of this study was to investigate the effect of administration of the probiotic Bacillus NP5 in rearing media on water quality, growth, and disease resistance of African catfish. The study consisted of three different concentrations of probiotic Bacillus NP5 - C: control, A: probiotic Bacillus NP5 of 1 x 109 CFU/mL, and B: probiotic Bacillus NP5 of 1 x 1010 CFU/mL, on the rearing media of African catfish for 45 days. Based on the results, the lowest significant ammonia (P
Keywords: Bacillus NP5, Clarias gariepinus, disease-resistant, probiotic, water quality